Faculty Participation in Teaching Improvement Programs - Botman, Elizabeth S.; Gregor, Alexander D. (Canadian Journal of Higher Education, 1984)
A study undertaken to explore faculty nonparticipation in teaching improvement programs is described. Faculty nonparticipation was viewed as a function of interacting personal and situational factors. Questionnaire results, representing 30 percent of the academic faculty at a major university, were compared along disciplinary lines and according to participation in instructional workshops. Responses of past participants and nonparticipants were compared in order to identify variables associated with nonparticipation in instructional development activities. Approximately one-quarter of the 213 respondents had participated in teaching improvement workshops at least once since 1971. Respondents from the Professions and Applied Sciences appeared generally most supportive of the concept of T.I.P. 's while respondents from the Faculty of Science appeared to be the least positive. The study results suggest that faculty nonparticipation in T.I.P. 's may be associated with: the professor's views about teaching and teaching improvement; the relative personal priority assigned to teaching; the perceived need for improvement in teaching skills; attitudes towards the teaching improvement program; awareness of available programs; and the perceived convenience of available programs. The perceived level of university support for good teaching was less clearly associated with nonparticipation, and perceived situational barriers were not found to be associated.